1994
DOI: 10.1002/path.1711740206
|View full text |Cite
|
Sign up to set email alerts
|

Expression of E‐cadherin (E‐CD) as related to other prognostic factors and survival in breast cancer

Abstract: A series of 208 breast cancer biopsies were analysed immunohistochemically for expression of E-cadherin (E-CD). Altogether, 72 per cent of the tumours showed E-CD positivity in over 50 per cent of cells, the staining being heterogeneous in nearly all tumours. In only 16 per cent of ductal carcinomas was positive staining seen in less than 1 per cent of cells. Expression of E-CD was not related to tumour diameter, nodal status, metastasis at diagnosis, histological grade, DNA ploidy, S-phase fraction, nuclear a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

10
89
1
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 19 publications
10
89
1
1
Order By: Relevance
“…Charpin's study (Charpin et al, 1997), also on frozen sections, noted that tumours with weaker E-CD expression were heterogeneous. Studies on paraffinembedded tumours, as in this study, have also observed distinct intratumoural variation in staining intensity (Lipponen et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Charpin's study (Charpin et al, 1997), also on frozen sections, noted that tumours with weaker E-CD expression were heterogeneous. Studies on paraffinembedded tumours, as in this study, have also observed distinct intratumoural variation in staining intensity (Lipponen et al, 1994).…”
Section: Discussionsupporting
confidence: 76%
“…Some (Gamallo et al, 1993;Lipponen et al, 1994;Gonzalez et al, 1999) have observed a relationship with histological grade and tumour type, but no other features. Maguire et al (1997), detecting E-CD by ELISA found no relationship with tumour size, node status or ER, but did associate early recurrence with lower E-CD levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This direct association was found to be 51% after accounting for chance agreement. While, Lipponen et al 39 demonstrated a similar direct association of E-CD expression with ER protein expression, other workers 30,40 did not observe any significant association between the two. It has been postulated that reversible down regulation of E-CD may occur by hypermethylation of the promoter region of E-CD expression.…”
Section: Discussionmentioning
confidence: 83%
“…Several studies indicate that reduced E-cadherin expression is an independent indicator of poor survival, particularly in node-negative patients [58][59][60][61]. However, other studies have found E-cadherin to be of little use in predicting clinical behavior of breast cancer patients [62]. Indeed, one study even noted that strong E-cadherin immunostaining correlated with poor survival [63].…”
Section: Discussionmentioning
confidence: 99%